Strategy To Increase Stock Prices (Study of Bank Sub Sectors Listed on the Indonesian Stock Exchange in 2022) - Nura'eni, Ai Dini; Rahwana, Kusuma Agdhi; Arif (Journal of Management, Economic, and Accounting, 2024)
This research aims to determine the condition of capital structure, profitability and share prices in the banking sub-sector, as well as to test and analyze the influence of capital structure as measured by the debt to equity ratio (DER) and profitability as measured by return on assets (ROA) on share price (closing price). This type of research uses quantitative research. The sample was taken using a purposive sampling method, namely 41 samples from 47 banking sectors listed on the Indonesia Stock Exchange in 2022. The secondary data source used came from the IDX.co.id website. The analysis was carried out using the multiple linear regression method using IBM SPSS version 25 software. The research results show that simultaneously capital structure (DER) and profitability (ROA) have a significant effect on stock prices. However, partial test results show different effects, capital structure (DER) does not have a significant effect on stock prices, while profitability (ROA) has a significant effect on stock prices.